Reduced Intensity transplantation vs chemotherapy in CR1. A prospective, pseudorandomized study in 50-70 year old AML patients - Brune, Mats; Kiss, Thomas; Anderson, Harald; Nicklasson, Malin; Delage, Robert; Finke, Jürgen; Gedde-Dahl, Tobias; Hébert, Josée; Höglund, Martin; Kaare, Ain; Lazarevic, Vladimir; Möllgård, Lars; et al. (SPRINGERNATURE, 2025)
The aim of this prospective, international multicenter, pseudorandomized study comparing RICT HCT to standard-of-care chemotherapy in intermediate- or high-risk AML patients 50-70 years using the donor versus no-donor concept. Part 1 included only patients with potential family donors (RD) at the date of HLA-typing of the first potential sibling or CR-date, if later. Part 2 allowed the inclusion of patients without a possible sibling donor using the start of an unrelated donor (URD) search as inclusion date. 360 patients were registered and 309 analyzed. The median follow-up was 47 months (1-168). There was no difference in overall survival (OS) between the RD (n = 124) and the Control (n = 77) groups (p = 0.50, 3-year OS RD: 0.41(95% CI; 0.32-0.50); Controls: 0.49 (95% CI; 0.37-0.59)). The main cause of death was relapse (67% RD; 88% Controls). In Part 2, the 3-year OS was 0.60 (95% CI 0.50-0.70) for URD-HCT (n = 86) and 0.37 (95% CI 0.13-0.62) for Controls (n = 20), respectively (p = 0.10). When analyzing transplanted patients (Part 2), the OS at 3-years was higher for URD-HCT than RD-HCT (0.67 (0.55-0.76) vs. 0.42 (0.26-0.57; p = 0.005). This study doesn't support elderly HLA-identical siblings as donors for older AML patients undergoing a RICT allogeneic HCT in first CR.